Réponses

2014-03-02T17:04:12+01:00


A= 5/18 - (3/36 - 1/36)

A= 5/18 - 2/36

A= 5x2 / 18x2 - 2/36

A= 10/36 - 2/36

A= 8/36

A= 2/9


B=17/12 -  (11/12 - 1/3)

B= 17/12 - (11/12 - 1x4 / 3x4)

B= 17/12 - (11/12 - 4/12)

B= 17/12 - 7/12

B= 10/12

B= 5/6


C= 11/6 - 2/3  + 1/6

C= 11/6 + 1/6 - 2/3

C= 12/6 - 2/3

C= 12/6 - 2x2 / 3x2

C= 12/6 - 4/6

C= 8/6

C= 4/3


D= 23/8 - 3/4 - 1/2

D= 23/8 - 3x2 / 4x2 - 1x4 / 2x4

D= 23/8 - 6/8 - 4/8

D= 17/8 - 4/8

D= 13/8


2014-03-02T17:05:25+01:00
A = 5/18-(3/36-1/36)
A = 5/18 - 2/36
A = 10/36 - 2/36
A = 8/36
A = 2/9

B = 17/12-(11/12-1/3)
B = 17/12 - (11/12 - 4/12)
B = 17/12 - 7/12
B = 10/12
B = 5/6

C = 11/6-2/3+1/6
C = 11/6 - 4/6 +1/6
C = 8/6
C = 4/3

D = 23/8-3/4-1/2

D = 23/8 - 6/8 - 4/8
D = 13/8